Peran mediasi collective self-esteem dalam meningkatkan kompetensi media sosial melalui kewarganegaraan digital di kalangan mahasiswa: The mediating role of collective self-esteem in enhancing social media competence through digital citizenship among college students - Islah, Fadhil Maliky; Helmi, Avin Fadilla (Persona:Jurnal Psikologi Indonesia, 2024)
College students face challenges in developing social media competencies that support their participation in digital citizenship. This study aimed to analyze the relationship between digital citizenship and social media competency mediated by collective self-esteem among college students (N = 736). The web-based study was used to collect data by convenience sampling and three measurement instruments, the digital citizenship scale (α= 0.90) to measure digital citizenship, the social media competence scale for college students (α= 0.92) to measure social media competence, and the collective self-esteem scale (α= 0.94) to measure collective self-esteem. The data were analyzed using Hayes mediation analysis with 5,000 percentile bootstrap samples and a 95% confidence interval. The results of the mediation test through jamovi (Version 2.3.2) showed that collective self-esteem played a role in mediating the relationship between digital citizenship and social media competence. However, the role of collective self-esteem as a mediator is not perfect because of its small effect. The findings prove that evaluating the student's national identity is indirectly a form of attitude toward maintaining a positive group (state) to control relational activities and citizenship by adopting social media. The findings emphasize the importance of strengthening college students' collective identity to support more positive and responsible use of social media within the context of digital citizenship.